Performance and Adoption of Improved Production Technology of Sesame (Sesamum indicum L.) in Bundelkhand region of Madhya Pradesh - Kumar, Ashish; Singh, D.K. (Indian Journal of Extension Education, 2012)
To understand economic feasibility of technology transfer and adoption in Sesame (Sesamum indicum L.), front line  demonstrations on improved variety (JTS-8), fertilizer application (30:60:20 NPK), plant protection (seed treatment with  Carbendazim 2 g/kg, foliar spray of Mancozeb and Endosulphan), full package of practices etc., a study was carried out  during the rainy season (Kharif) of 2008, 2009 and 2010. Improved technology had given higher yield in all respects.  Improved variety 'JTS 8' gave 17 per cent more yield (322 to 410 kg/ha) over farmers practices and ` 8750/ ha. in term of  net return. The yields obtained under fertilizer management were 18 per cent (314-502kg/ha), plant protection 22 per cent  (505-314kg/ha), weed control 27 per cent (513-328kg/ha) and full package of practices 32 per cent (585-348kg/ha).  Minimum technology gap (148) existed in fertilizer management component of technology demonstration, while  minimum extension gap (88) existed in improved variety component of technology demonstrations.
Keywords: Improved production technology; demonstrations; fertilizer management